Experimental infections with Paracoccidioides brasiliensis obtained from armadillos: Comparison to clinical isolates - Nishikaku, Angela Satie; Peraçoli, Maria Terezinha S. [UNESP]; Bagagli, Eduardo [UNESP]; Sugizaki, Maria Fátima [UNESP]; Sartori, Alexandrina [UNESP] (FapUNIFESP (SciELO), 2008)
Paracoccidioides brasiliensis causes paracoccidioidomycosis (PCM) that is one of the most prevalent systemic human mycoses in Latin America. Armadillos show a high incidence of PCM infection and could, therefore, be a natural reservoir for this fungus. In this study were compared the virulence profiles of isolates obtained from nine-banded armadillos (Dasypus novemcinctus) (PbT1 and PbT4) and isolates from PCM patients (Pb265 and Bt83). Pathogenicity was evaluated by fungal load and analysis of colony morphology. Immunity against the fungus was tested by delayed type hypersensitivity test (DTH) and antibody quantification by ELISA. The higher virulence of PbT1 and PbT4 was suggested by higher fungal load in spleen and lungs. Armadillo isolates and Bt83 presented a cotton-like surface contrasting with the cerebriform appearance of Pb265. All isolates induced cellular and humoral immune responses in infected BALB/c mice. DTH reactions were similarly induced by the four isolates, however, a great variability was observed in specific antibody levels, being the highest ones induced by Bt83 and PbT4. The present work confirms that armadillos harbor P. brasiliensis, whose multiplication and induced immunity in experimentally infected mice are heterogeneous, resembling the behavior of isolates from human PCM. This study reinforces the possibility that armadillos play an important role in the biological cycle of this pathogen. © 2008 by The Brazilian Journal of Infectious Diseases and Contexto Publishing. All rights reserved.
Keywords: Armadillos; BALB/c mice; Infection; Paracoccidioides brasiliensis